Zimoziół północny Linnaea borealis L. w północnej części Niziny Południowopodlaskiej - Ciosek, Marek; Krechowski, Janusz; Piórek, Katarzyna; Sikorski, Roman; Trębicka, Agata (Leśne Prace Badawcze, 2026)
Linnaea borealis, the twinflower, is considered a critically endangered species in the Południowopodlaska Lowland. The disappearance of the twinflower is mainly caused by habitat changes resulting from forest management, but also light deficiency due to the increase in canopy cover and growth of the shrub layer (processes of succession). The aim of the paper is to present the actual distribution and phytosociological characteristics of L. borealis in the northern part of the Południowopodlaska Lowland. In this region, only three out of ten known areas of occurrence (Werchliś, Serpelice, Grala-Dąbrowizna) have endured to the present day. The twinflower occurs in pine forest, Peucedano-Pinetum , and mixed forest, Querco roboris-Pinetum , communities. A decrease in the ground cover of twinflower populations was observed in all existing twinflower locations. Although the area covered by the Linnaea borealis population in Werchliś increased tenfold during the last 20 years (from about 200 m 2 in 1993 to 1970 m 2 in 2013), its cover-abundance according to the Braun-Blanquet scale decreased from 5 to 3. The increase in the area covered by the twinflower population together with the accompanying decrease in cover-abundance is probably not a manifestation of species dynamics but rather a response to disadvantageous environmental changes (growth of canopy cover and shrub layer). Progressive light reduction can initiate the process of fragmentation of a population. A decrease in the cover-abundance of the L. borealis population (from 4 to 2) was also observed in Serpelice. Its area was reduced to half of its original size due to anthropogenic destruction of this location. In the third region, Grala-Dąbrowizna, also the negative effects of competitive species (e.g. Vaccinium myrtillu s, V. vitis-idaea ) are considered.